2020
DOI: 10.1002/pssb.202000055
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of Steel Film by Hydrogen Absorption at Cathodic Potential in Electrolyte

Abstract: An ≈4 nm FeCrNi film, deposited on a Ru/B4C multilayer (ML), is used to study cathodic hydrogen charging in electrolyte. A thin film on a ML allows obtaining precise quantitative information on surface metal composition and oxidation state using the X‐ray standing wave technique combined with near‐edge X‐ray absorption spectroscopy. The metal composition is found being close to the composition of stainless steel (SS) 304, and, as for bulk steel, the outer 2 nm passive layer, consisting of oxidized iron and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…[23] Thus, the thin films appear to be reflecting the behavior of the investigated bulk steel surface region. This confirms our earlier conclusions that steel thin films represent valuable replicas of the surface region of stainless steel [23,26] despite the fact that the "production" histories of the bulk steel samples and the thin films are obviously quite different. Analysis of the XANES data of the 50 nm film reveals that 30% of the iron is adopting the ferrite structure, which can be compared with the GIXRPD results on the polished steel sample.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…[23] Thus, the thin films appear to be reflecting the behavior of the investigated bulk steel surface region. This confirms our earlier conclusions that steel thin films represent valuable replicas of the surface region of stainless steel [23,26] despite the fact that the "production" histories of the bulk steel samples and the thin films are obviously quite different. Analysis of the XANES data of the 50 nm film reveals that 30% of the iron is adopting the ferrite structure, which can be compared with the GIXRPD results on the polished steel sample.…”
Section: Discussionsupporting
confidence: 89%
“…We recently reported that cathodic hydrogen loading is stressing the steel surface immensely. [26] However, with concentrations in the ppm range, it is questionable whether the hydrogen concentration in steel following hydrogen in-diffusion under ambient conditions [41,42] could introduce sufficient strain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations